Complete mitochondrial genome of the Eurasian siskin, Spinus spinus (Passeriformes: Fringillidae). (3rd May 2016) - Kan, Xianzhao; Ren, Qiongqiong; Wang, Ping; Jiang, Lan; Zhang, Liqin; Wang, Ying; Zhang, Qin
Abstract: The Eurasian siskin ( Spinus spinus ), also called the European siskin, common siskin or just siskin, is found throughout Europe and Asia. In this study, the complete mitochondrial genome of S. spinus was determined to be 16, 828 bp. The size of protein-coding genes (PCGs) in the S. spinus mitochondrial genome was 11, 400 bp. The longest PCG of S. spinus mtDNA was nad5 (1818 bp), whereas the shortest is atp8 (168 bp). The nad6 gene of S. spinus mitogenome had strong skews of T versus A (−0.54), and G versus C (0.64). According to the distribution of the conserved motifs in other avian CRs, the CR of S. spinus can be divided into three domains: ETAS domain I, central conserved domain II, and CSB domain III.